Fabrication of Fresnel plates on optical fibres by FIB milling for optical trapping, manipulation and detection of single cells - Rita S. Rodrigues Ribeiro (Nature Portfolio, 2017)
Abstract The development of economical optical devices with a reduced footprint foreseeing manipulation, sorting and detection of single cells and other micro particles have been encouraged by cellular biology requirements. Nonetheless, researchers are still ambitious for advances in this field. This paper presents Fresnel zone and phase plates fabricated on mode expanded optical fibres for optical trapping. The diffractive structures were fabricated using focused ion beam milling. The zone plates presented in this work have focal distance of ~5 µm, while the focal distance of the phase plates is ~10 µm. The phase plates are implemented in an optical trapping configuration, and 2D manipulation and detection of 8 µm PMMA beads and yeast cells is reported. This enables new applications for optical trapping setups based on diffractive optical elements on optical fibre tips, where feedback systems can be integrated to automatically detect, manipulate and sort cells.